2000
DOI: 10.2139/ssrn.230010
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, Knowledge Transfer, and Organizational Forms

Abstract: Employees are motivated intrinsically as well as extrinsically. Intrinsic motivation is crucial when tacit knowledge in and between teams must be transferred. Organizational forms enable different kinds of motivation and have different capacities to generate and transfer tacit knowledge. Since knowledge generation and transfer are essential for a firm's sustainable competitive advantage, we ask specifically what kinds of motivation are needed to generate and transfer tacit knowledge, as opposed to explicit kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
770
1
24

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 593 publications
(811 citation statements)
references
References 89 publications
16
770
1
24
Order By: Relevance
“…Obviously that process is not an accurate description of reality as shareholders and stakeholders had to painfully experience during this financial crisis and various other crises before. A large body of research has previously debunked such a model as flawed (Frey, 2007;Kahneman et al, 1982Kahneman et al, , 1986Osterloh and Frey, 2000). In addition, the assumptions of economics regarding human behavior have long been proven incomplete or wrong.…”
Section: The Economistic Basis Of Corporate Governancementioning
confidence: 99%
“…Obviously that process is not an accurate description of reality as shareholders and stakeholders had to painfully experience during this financial crisis and various other crises before. A large body of research has previously debunked such a model as flawed (Frey, 2007;Kahneman et al, 1982Kahneman et al, , 1986Osterloh and Frey, 2000). In addition, the assumptions of economics regarding human behavior have long been proven incomplete or wrong.…”
Section: The Economistic Basis Of Corporate Governancementioning
confidence: 99%
“…Whereas their systematic theoretical treatment remains to be a task of the future, important steps toward this goal are already being made. Particularly noteworthy in this connection is the increasing recognition of the importance of intrinsic motivation as a factor of economic organization of for-profit firms (see e.g., Kreps, 1997;Osterloh & Frey, 2000). Indeed, the neglect of intrinsic motivation has become one of the major reasons for criticizing the Williamson's version of the transaction cost theory which does not pay enough attention to the tendency of hierarchical control to crowd out intrinsic motivation of employees.…”
Section: Intrinsic Motivation In Organizational Economics: a More Genmentioning
confidence: 99%
“…Motivational factors might include, for example, the lack of motivation to give and receive knowledge (Szulanski, 1996;Carter, et al, 2004;Gupta and Govindarajan, 2000). Osterloh and Frey (2000) emphasise that a distinction needs to be made between extrinsic and intrinsic motivation. Motivation is extrinsic if employees are able to satisfy their needs indirectly, especially through monetary compensation.…”
Section: Ethical Dimensions Of Knowledge Transfer In Global Organizatmentioning
confidence: 99%
“…Extensive research has shown that intrinsically motivated and extrinsically motivated employees behave differently with respect to pressure and rewards. In particular, Osterloh and Frey (2000) suggest that transfer of tacit knowledge is strongly related to intrinsic motivation. Whereas explicit knowledge is relatively easy to value and monitor, the same is not the case with tacit knowledge.…”
Section: Ethical Dimensions Of Knowledge Transfer In Global Organizatmentioning
confidence: 99%
See 1 more Smart Citation